What is the role of men in connecting women to cash crop markets? Evidence from Uganda - Ambler, Kate; Jones, Kelly M.; O'Sullivan, Michael (International Food Policy Research Institute, 2018)
Programs that seek to increase women’s participation in marketing activities related to the principal household economic activity must involve men if they are to be successful. In this paper we analyze take-up of a project that sought to increase women’s involvement in sugarcane marketing and sales by encouraging the registration of a sugarcane block contract in the wife’s name. We find that men who are more educated and live in households with higher wealth and expenditures are more likely to agree to the registration. Households with more cane blocks and in which the wife is already more involved in cane activities are also more likely to participate. Overall, take-up is high at 70%, and remains high even in those groups that are less likely to take-up. Additionally, we find that blocks transferred to women are not of lower quality or value than those kept by men, though they are smaller and closer to the home. These results suggest that simple encouragement can be an effective tool to nudge men to include their wives in household commercial activities.